IRON, COPPER AND MOLYBDENUM IN THE DIFFERENT BODY PARTS O F SOME CLUPEOIDS - Rao, T Appa (Indian Journal of Fisheries, 2011)
The amounts of ifon, copper and molybdenum in the different tissues ofeight species of clupeoids belonging to the genera Stolephonis, Thryssa and Sardinellawere determined. Irt all the species, the concentration of each element didnot bear any relation to Mze. It was observed that iron and copper were concentratedmore in heart and liver than in stomach, pyloric caecae, kidneys, ovaries,testes, flesh and bone.